(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the problems that arise in the process of translating world literature into Uzbek. Factors such as the artistic expression of the translation, cultural context, semantic differences, and changes in language structures are studied. Suggestions are made for improving the translation and the significance of the results for literary communication is emphasized.